2019
DOI: 10.1364/boe.10.002996
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of skin disorders in type 1 diabetic mice by in vivo optical imaging

Abstract: Diabetes can affect the skin structure as well as the cutaneous vascular permeability. However, effective methods to quantitatively evaluate diabetes-induced skin disorders in vivo are still lacking. Here, we visualized the skin by using in vivo two-photon imaging and quantitatively evaluated the collagen morphology. The results indicated that diabetes could cause a significant reduction in the number of collagen fibers and lead to the disorder of skin collage fibers. And, the classic histological analysis als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…A recent study have verified that UVB irradiation caused the skin dermis became thinner after H&E staining ( Blackstone et al, 2020 ), our study found the same result. In our study, the number of collagen fibers in the skin of mice with UVB-induced skin damage decreased, and at the same time, collagen fibers appeared atrophy, breakage and stickiness ( Feng et al, 2019 ). Otherwise, the number of mast cells in the dermis layer increases significantly after UVB irradiation, which indicate the aggravation of skin inflammation ( Kim et al, 2014a ).…”
Section: Discussionmentioning
confidence: 55%
“…A recent study have verified that UVB irradiation caused the skin dermis became thinner after H&E staining ( Blackstone et al, 2020 ), our study found the same result. In our study, the number of collagen fibers in the skin of mice with UVB-induced skin damage decreased, and at the same time, collagen fibers appeared atrophy, breakage and stickiness ( Feng et al, 2019 ). Otherwise, the number of mast cells in the dermis layer increases significantly after UVB irradiation, which indicate the aggravation of skin inflammation ( Kim et al, 2014a ).…”
Section: Discussionmentioning
confidence: 55%
“…In vivo, OTC has been applied to the skin for visualizing blood flow in the skin (Vargas et al, 2003;Wang et al, 2013aWang et al, , 2013bZhu et al, 2010) and cutaneous vascular permeability in mice suffering from diabetes (Feng et al, 2019) and for improving the imaging of diseased skin in a variety of skin diseases such as hemangioma and epidermoid cyst (Shan et al, 2012) as well as increasing laser penetration into the dermis during tattoo removal (Liu et al, 2015).…”
Section: Applications Of Optical Clearing and Volumetric Imagingmentioning
confidence: 99%
“…With this method, it is possible to generate a 3D image without physically sectioning the tissue. OTC can be used in ex vivo 3D anatomical investigations to study skin pathology, for instance, epidermal hyperplasia in psoriatic skin (Abadie et al, 2018) or neuronal innervation in pruritic skin (Tan et al, 2019) as well as in in vivo skin imaging to measure dermal blood flow (Wang et al, 2013b) and alterations in skin structure in mice with diabetes (Feng et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Tissue optical clearing (TOC) is a convenient technique to increase the penetration depth of thick tissues [17][18][19][20][21][22]. The replacement of free water with optical clearing agents of higher refractive index, such as glycerin, causes refractive index matching between the scatterers and their surrounding media to reduce the scattering coefficient of biological tissues, which is often considered as one of the major mechanisms of TOC [23][24][25].…”
Section: Introductionmentioning
confidence: 99%